THE MOLDOVAN BANK FRAUD (2012-2015). A process tracing analysis of the Moldovan $1 billion money laundering - VARZARI, Alexandrina (Economy and Sociology, 2021)
In the 2012-2015 period, $1 billion have been stolen from three Moldovan banks, which is the equivalent of 12% of the country’s GDP. The highly fraudulent environment in the RM allowed for the successful application of fraudulent schemes for three years, without it being seized and frozen. This paper seeks to decipher the schemes that were applied as well as argue how the integration into the European Union would have lowered the corruption and thereby prevent the fraud from happening. Even though several scholars discussed the bank fraud and how it affected the relationship between Moldova and the EU, they do not address how the steps of integration into the European Union could gradually regulate the level of corruption in the RM and subsequently eliminate the possible methods of committing the bank fraud. Through a comparative analysis of Romania and the Republic of Moldova, I aim to demonstrate that the difference between the level of corruption and the stability of the banking system in these two countries is due to EU membership. Further, through secondary analysis of qualitative data, and semi-constructed interviews, I conclude that, in theory, my argument holds – the instruments the EU applies on the candidate countries would not have allowed the fraudulent schemes to be put into action. However, the EU failed to apply the conditionality concept on Romania and thus, it is possible that the money laundering in the RM could have happened even if it had been a member of the EU.